2022
DOI: 10.3390/ijerph19106183
|View full text |Cite
|
Sign up to set email alerts
|

Has China’s New Round of Collective Forest Reforms Reduced Forest Fragmentation? A Case Study of the Beijing–Tianjin–Hebei Region

Abstract: The new wave of reform of collective forestland tenure (NRCFT) in China is considered an important policy for achieving sustainable management of forest resources. The purpose of this study is to investigate the influence of NRCFT on forest fragmentation in the Beijing–Tianjin–Hebei region of China based on a fixed-effects model. The forest fragmentation was analyzed based on the remote sensing images of Landsat and landscape pattern indices in the Beijing–Tianjin–Hebei region from 2000 to 2018. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Human activities and policies are the primary factors affecting LULC changes in the Loess Plateau (Zheng et al, 2019). Since implementing the GGP in 1999, the government's awareness consciousness of woodland conservation has gradually increased, and forest cover has grown rapidly (Yang et al, 2023; Zhu et al, 2022). In addition, large cropland areas have been used for afforestation projects.…”
Section: Discussionmentioning
confidence: 99%
“…Human activities and policies are the primary factors affecting LULC changes in the Loess Plateau (Zheng et al, 2019). Since implementing the GGP in 1999, the government's awareness consciousness of woodland conservation has gradually increased, and forest cover has grown rapidly (Yang et al, 2023; Zhu et al, 2022). In addition, large cropland areas have been used for afforestation projects.…”
Section: Discussionmentioning
confidence: 99%
“…Some empirical studies have shown that the CFTR did not increase households' investment in forestry production. He et al (2020) argued that the CFTR did not significantly enhance the level of forestry investment as expected [14][15][16].…”
Section: Introductionmentioning
confidence: 92%
“…The interaction term between collective forestland tenure reform and rural household differentiation is introduced to be identified on the basis of Equation ( 1), and the specific model is set as Equation (2) to test the moderating effect of rural household differentiation on collective forestland tenure reform and rural household forestry inputs (2).…”
Section: Empirical Test Modelmentioning
confidence: 99%
“…First, the security effect. Most studies have found that collective forestland tenure reform makes tenure in forests more stable and reduces the number of disputes over forestland tenure [2]. Long-term stable land tenure ensures that rural households' land returns are not appropriated by the government or institutions [3], reduces the uncertainty of future returns [4], and stimulates investment by influencing the expected rewards of land [5].…”
Section: Introductionmentioning
confidence: 99%